Distributions in Motion : Economic Growth, Inequality, and Poverty Dynamics - Ferreira, Francisco H.G. (2012)
The joint determination of aggregate economic growth and distributional change has been studied empirically from at least three different perspectives. A macroeconomic approach that relies on cross-country data on poverty, inequality, and growth rates has generated some interesting stylized facts about the correlations between these variables, but has not shed much light on the underlying determinants. "Meso-" and microeconomic approaches have fared somewhat better. The microeconomic approach, in particular, builds on the observation that growth, changes in poverty, and changes in inequality are simply different aggregations of information on the incidence of economic growth along the income distribution. This paper reviews the evolution of attempts to understand the nature of growth incidence curves, from the statistical decompositions associated with generalizations of the Oaxaca-Blinder method, to more recent efforts to generate "economically consistent" counterfactuals, drawing on structural, reduced-form, and computable general equilibrium models.